2010
DOI: 10.1002/lary.21142
|View full text |Cite
|
Sign up to set email alerts
|

Increased amphiregulin expression as a biomarker of cholesteatoma activity

Abstract: Amphiregulin is overexpressed in epithelial tissues of human cholesteatoma. Significant relationships were identified between increased amphiregulin expression levels and the extent of cholesteatoma migration and bone erosion. Our study results indicate amphiregulin is a potential biomarker of early cholesteatoma disease processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…This was more pronounced in children in whom cholesteatomas were more aggressive than adults [82]. Another study conducted by Macias et al [83] investigated the role of amphiregulin as a biological marker for cholesteatoma activity. Amphiregulin gene expression was found higher in cholesteatoma tissues as compared to skin control tissues and the increased expression was inversely related to the stage of disease progression [83].…”
Section: Mechanisms Of Bone Resorption In Cholesteatomamentioning
confidence: 99%
See 2 more Smart Citations
“…This was more pronounced in children in whom cholesteatomas were more aggressive than adults [82]. Another study conducted by Macias et al [83] investigated the role of amphiregulin as a biological marker for cholesteatoma activity. Amphiregulin gene expression was found higher in cholesteatoma tissues as compared to skin control tissues and the increased expression was inversely related to the stage of disease progression [83].…”
Section: Mechanisms Of Bone Resorption In Cholesteatomamentioning
confidence: 99%
“…Another study conducted by Macias et al [83] investigated the role of amphiregulin as a biological marker for cholesteatoma activity. Amphiregulin gene expression was found higher in cholesteatoma tissues as compared to skin control tissues and the increased expression was inversely related to the stage of disease progression [83]. Many other proliferation markers were discussed in the literature including CK 13&16, epidermal growth factor, IL-1, TGF-α, keratinocyte growth factor, proliferating cell nuclear antigen, tolemerase, and Ki-67.…”
Section: Mechanisms Of Bone Resorption In Cholesteatomamentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade it has become obvious that there is not one gene suitable for use of normalisation for all tissue types [ 40 ]. In the field of middle ear research many different genes have been used, such as B2M [ 52 ], PPIA [ 9 ], ACTB [ 33 , 34 ], HPRT1 [ 35 ] and GAPDH [ 36 39 ]. Interestingly, all articles published to this date use only one gene for normalisation, even though it has been abundantly shown that this is not sufficient for reliable analysis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…QPCR has been used in several studies related to diseases of the middle ear. However, there seems to be little consensus as to which reference genes to use for normalisation, leading to the use of several different genes without proper establishment of which genes are appropriate [9,[31][32][33][34][35][36][37][38][39]. To be able to obtain reliable results the use of stably expressed reference genes for normalisation is essential [40].…”
Section: Introductionmentioning
confidence: 99%